Necessity of a fintech global regulation (2020)
This article analyzes the need for international regulation for Fintech businesses. First, a brief analysis is made of the importance of the topic and the risks of the lack of good regulation. Subsequently, different cases of regulation are analyzed at the level of the traditional financial sector, as well as of some States that are considered decisive for the Fintech business, including Colombia, which has shown a good development of such ventures at the regional level. To achieve the task that we set ourselves, the deductive method was used, starting from the generality of the available information, and subsequently to an analysis of specific cases. Regarding the case study, it was a comparative study to offer a broader view of what should be the best applicable regulation. After this analysis, it was concluded that currently no state model would serve as an international model law and that what is required is a dialogue between States and businessmen to be able to approach the issue from different perspectives, in such a way that ensure economic growth and protection of both the economy and consumers internationally.